Penyuluhan Menghadapi Era New Normal Covid – 19 dan Bisnis di Masa Less Contact Economy di Rumah Baca Komunitas Yogyakarta - Annisa Khumaira; Fitri Maulidah Rahmawati (Universitas Lancang Kuning, 2023)
Abstract Since Covid-19 was declared a global pandemic, many changes have occurred in people's social life. The need to maintain physical distance has made an impact in various fields, one of which is that there is a recession in various countries, and Indonesia gives a signal that it will experience this, indicated by the country's gross income of -5.32%. In dealing with this, the government has imposed a